Efecto de la fertilizacion quimica y organica en el cultivo de arroz (Oryza sativaL) con la lamina de agua - Avilés Rosado, Danny Roberto (2012)
This research was conducted at Hacienda La Etelvina, 1 kilometer from the Cantonal Head of Colimes, Province Guayas, whose location is latitude 1 º 33 'and longitude 80 ° 1 `. The selected site topography is flat with a type of clay loam soil, the duration of the fieldwork was 120 days 2011-2012. Metrological conditions in the area. Temperature 24.9 ° C, relative humidity 83%, light years heliophany 744.8 hours, precipitation 2229 mm / year.